1996
DOI: 10.1111/j.1439-037x.1996.tb00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐destructive Determination of Leaf Chlorophyll Content in Four Crop Species1

Abstract: A recent non‐destructive technique allows estimation of leaf chlorophyll content using the portable SPAD‐502 chlorophyll meter. Measurements were taken on four species (winter wheat, maize, soyabean and tobacco) subjected to different nitrogen regimes or senescence status and the: non‐destructive readings were compared with analytical results obtained by solvent extraction. In general, the relationship between the SPAD measurement and the analytical result was not linear and species was a factor in three out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 14 publications
5
68
0
3
Order By: Relevance
“…Likewise, the equations were found to be species-specific when leaves of similar age were considered (Castelli et al, 1996;Pinkard et al, 2006). When the data for the four species were pooled per leaf stage, regression residuals revealed a positive statistical correlation with fresh LMA in all cases (P < 0.01, data not shown).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Likewise, the equations were found to be species-specific when leaves of similar age were considered (Castelli et al, 1996;Pinkard et al, 2006). When the data for the four species were pooled per leaf stage, regression residuals revealed a positive statistical correlation with fresh LMA in all cases (P < 0.01, data not shown).…”
Section: Discussionmentioning
confidence: 82%
“…In many cases, non-linear equations have been used to explain the relationship between the two parameters better due to non-uniform distribution of chlorophyll and differential scattering and reflection of light at the wavelengths used (Markwell et al, 1995;Monge and Bugbee, 1992;Uddling et al, 2007). In this sense, several studies have reported that calibration should be speciesspecific (Castelli et al, 1996;Pinkard et al, 2006;Uddling et al, 2007;Yamamoto et al, 2002), and that it may even be affected by growing conditions (Campbell et al, 1990;Jifon et al, 2005). Another issue, although little addressed (Thompson et al, 1996), is that leaf structural parameters (LMA, tissue density, water content, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between SPAD values and chlorophyll concentration has been investigated in a variety of different species, and has been found to display considerable interspecific variation (Castelli et al 1996;Uddling et al 2007). This variability is presumed to be due to structural differences between the leaves of different species, causing different light reflection or scattering effects.…”
Section: Introductionmentioning
confidence: 99%
“…Em plantas de milho, a concentração de N, de clorofila e as leituras fornecidas pelo SPAD-502 estão positivamente correlacionadas (Castelli et al, 1996;Argenta et al, 2001), exceto nos estádios iniciais de desenvolvimento em que a leitura realizada com o SPAD tem sua precisão reduzida (Argenta et al, 2001). Em situações em que a disponibilidade de N é grande, as leituras do SPAD-502 e o conteúdo de clorofila são pouco correlacionados, porque o potencial do sistema fotossintético já se encontra estabelecido e atuante na conversão de energia luminosa em energia química, e o excedente de N se encontra na forma de outros compostos de reserva (Argenta et al, 2001).…”
Section: Calibration Of a Minolta Spad-502 Chlorophyll Meter For Evalunclassified
“…Os valores dos coeficientes de determinação foram muito próximos nos dois modelos utilizados, discordando dos relatos encontrados na literatura que indicam que a correlação entre a clorofila foliar e as leituras do SPAD-502 no milho não é linear (Castelli et al, 1996). Apesar da semelhança dos coeficientes de determinação entre os modelos testados, os parâmetros da equação ajustada não foram significativos em ambos os extratores (Tabela 1).…”
Section: Calibration Of a Minolta Spad-502 Chlorophyll Meter For Evalunclassified